MAQĀṢID AL-SHARI'AH THEORY BY IMAM AL-SYĀṬIBĪ - Azis, Muh. Ilham; Eril, Eril; Taqiyuddin BN, Andi Muh.; Salam, Abdul; Arief, Ahmad (ANAYASA : Journal of Legal Studies, 2024)
The purpose of this study is to explain the theory and application of Maqāṣid al-Syari'ah from al-Syāṭibī's perspective. This research is qualitative, the type of research is library research. The data collection method used is a literature study. The results showed that; First, Maqāṣid al-Syari'ah is the central theme that became the foundation of Imam al-Syatibi in determining the law. According to Imam al-Syatibi, the main purpose of Maqāṣid al-Syari'ah is to organize the natural order by realizing maslahah and avoiding damage. Departing from the purpose of istinbat all laws in Islam which is the essence of maqasid al-Syariah that is implied and explicit, it is impossible to realize hifz al-din with the intention or purpose of neglecting hifz al-nafs, hifz al-nasl, hifz al-mal, and hifz al-'aql. Second, the application of Maqāṣid al-Shari'ah can be seen in the adoption of three maslahat, namely primary, secondary, and tertiary maslahat in contemporary muamalah. For example, the application of primary maslahat in the use of AstraZeneca vaccine which contains elements from pigs. Furthermore, the application of secondary maslahat to the practice of Islamic mutual funds is considered very urgent, because not a few have property, but are unable to manage or organize it. As for the application of tertiary maslahat in transactions via telephone, internet, instagram, WhatsApp, and other social media applications.